Atherosclerosis as Extrahepatic Manifestation of Chronic Infection with Hepatitis C Virus. (13th January 2016) - Voulgaris, Theodoros; Sevastianos, Vassilios A.
Abstract : Chronic hepatitis C virus infection is associated with significant morbidity and mortality, as a result of progression towards advanced natural course stages including cirrhosis and hepatocellular carcinoma. On the other hand, the SVR following successful therapy is generally associated with resolution of liver disease in patients without cirrhosis. Patients with cirrhosis remain at risk of life-threatening complications despite the fact that hepatic fibrosis may regress and the risk of complications such as hepatic failure and portal hypertension is reduced. Furthermore, recent data suggest that the risk of HCC and all-cause mortality is significantly reduced, but not eliminated, in cirrhotic patients who clear HCV compared to untreated patients and nonsustained virological responders. Data derived from studies have demonstrated a strong link between HCV infection and the atherogenic process. Subsequently HCV seems to represent a strong, independent risk factor for coronary heart disease, carotid atherosclerosis, stroke, and, ultimately, CVD related mortality. The advent of new direct acting antiviral therapy has dramatically increased the sustained virological response rates of hepatitis C infection. In this scenario, the cardiovascular risk has emerged and represents a major concern after the eradication of the virus which may influence the life expectancy and the quality of patients' life.